1990
DOI: 10.1099/00221287-136-6-1091
|View full text |Cite
|
Sign up to set email alerts
|

Yersinia enterocolitica immunodominant 60 kDa antigen, common to a broad range of bacteria, is a heat-shock protein

Abstract: Monoclonal antibodies (mAbs) against the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 35 publications
(23 reference statements)
1
33
0
Order By: Relevance
“…MAb was prepared by the method described previously [25]. The 60-kDa antigen derived from H. pylori TK 1029, partially purified by extraction from the separation gel by SDS-PAGE.…”
Section: Preparation Of Monoclonal Antibodiesmentioning
confidence: 99%
“…MAb was prepared by the method described previously [25]. The 60-kDa antigen derived from H. pylori TK 1029, partially purified by extraction from the separation gel by SDS-PAGE.…”
Section: Preparation Of Monoclonal Antibodiesmentioning
confidence: 99%
“…mAbs, termed 5C3 and 3C8, directed to Y. enterocolitica HSP60, were prepared as described previously (20,21). mAb3C8 with the broadest reactivity could recognize Gram-negative and Gram-positive rods.…”
Section: Hiroyukimentioning
confidence: 99%
“…3, Table 1). Immunoblot analysis was performed by the methods previously (21). The results of the immunoblot analysis indicated that 3C8 reacted with all 60-kDa antigens of the cells used, suggesting that leucine, glycine and valine detected in the amino acid sequences might be responsible for the reaction with 3C8.…”
Section: Hiroyukimentioning
confidence: 99%
“…To detect HSP antigens, monoclonal antibodies against Helicobacter pylori HSP 60 (Wako Pure Chemical Industries, Ltd., Osaka, Japan) were used 25) . Grown cells of isolated mycoplasma strains including M. salivarium ATCC 23060 and M. orale ATCC 23714 were also examined in this study.…”
Section: Production Of Hspmentioning
confidence: 99%